"BATIK KROYA” DALAM PERSPEKTIF ORIENTASI PEMBELAJARAN PADA ANAK USIA SEKOLAH DASAR DI SD N PEKUNCEN 01 KECAMATAN KROYA CILACAP - Fery Setyaningrum (Journal of Contemporary Indonesian Art, 2018)
The purpose of this research are (1) Describe the characteristics of "Kroya batik" in the element of kesenirupaan, (2) Describe the application of "Kroya batik" in elementary school children in Pekuncen 01 Kroya Primary School, Cilacap District in the context of kesenirupaan. (3) Describe the review "batik Kroya" in the understanding of the five orientations of educational attainment through the concept of Gage and Berliner. The research method using qualitative descriptive research approach, the subject of this research is the students of grade V Pekuncen 01 Kroya Primary School. Techniques of data collection using observation / controlled observation, interviews, and document studies. Data were analyzed through data reduction steps, data presentation and conclusion drawing or verification. The result of this research are (1) Kroya batik characteristic in the form of physical nature symbol in environment in Kroya Regency of Cilacap and the combination of point line, color, field, texture on the visual elements and typical design principles, (2) The process of application first batik motive in beginning by making batik design (mal technique), canting, menyolet (giving color), giving hard water, washing, color, washing, boiling, dried, (3) result of batik learning process at student of Pekuncen 01 Kroya Primary School is education can leads to an increase in the value of the personality (Development Regulatory), Education can develop regulatory affective, Education can increase creativity and cognition (Creativity & cognition), Education can increase curiosity, Education can create sensitivity. Keywords : Batik, Learning Orientation, Elementary School Age Children